Interleukin 27 inhibits cytotoxic T-lymphocyte-mediated platelet destruction in primary immune thrombocytopenia - Zhou, Hai (Blood, 2014)
Cytotoxic T-lymphocyte (CTL)-mediated platelet destruction and aberrant cytokine profiles play important roles in the pathogenesis of primary immune thrombocytopenia (ITP). Interleukin-27 (IL-27) has pleiotropic immunomodulatory effects. However, the effect of IL-27 on CTL activity in ITP has not been reported. In the present study, platelets from ITP patients were cultured with autologous CTLs in the presence of IL-27. We found that IL-27 could inhibit CTL-mediated platelet destruction. In these IL-27–treated CTLs, granzyme B and T-bet expression decreased significantly, whereas granzyme A, perforin, and eomesodermin were not affected. To further investigate the role of granzyme B in CTL-mediated platelet destruction, granzyme B inhibitor was added and platelet apoptosis was significantly inhibited. These results suggest that IL-27 negatively regulates CTL cytotoxicity toward platelets in ITP by decreasing granzyme B expression, which is associated with reduced T-bet expression. IL-27 may have a therapeutic role in treating ITP patients.